APLIKASI MONITORING KERJA PRAKTIK MAHASISWA PROGRAM STUDI SISTEM KOMPUTER - Salma Al Rasyid, Ikhwan Ruslianto, (SEMIRATA 2015, 2015)
Practical work subject is one of media for students to improve their knowledge that they already gained from campus. Every student that taking practical work subject can consult with their supervisor in order to get direction about what they should do when they took the subject. However, during consultation, both lecturer and the student didnâ€™t have record or note in digital form which can be accessed anytime and anywhere. Other than that, there is no control or recording from each student and lecturer that cause administration section work harder to monitor student progress. Because of that System Computer major in Tanjungpura University need monitoring application to monitor practical work students. System that will be created to ease control and recording for both administration section and lecturer for supervise practical work student. Â  Keyword: practical work student, monitoring, track record Â